Green financial development improving energy efficiency and economic growth: A study of CPEC area in COVID-19 era - Linyun Zhang; Feiming Huang; Lu Lu; Xinwen Ni (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2021)
This study seeks to evaluate the effect of green financial development, improving energy efficiency and economic growth on Covid-19 tenure. For this, the CPEC area is recommended to look into. Present study revealed the energy economic negative repercussions of Covid-19 impacts. It is assumed that, in China and Pakistan, economic expansion, trade openness, financial development, and urbanization coexist. To verify the postulated impacts of economic activity on the environment, we do Johansen cointegration, error correction, and Granger causality tests. We discovered that economic growth, energy consumption, trade openness, financial development, and urbanization had a long-term relationship to CO2 emissions in Pakistan. Urbanization is the only macroeconomic factor with a detrimental effect on carbon emissions. As with China, no cointegration is found across variables, but unidirectional causality from energy consumption and economic growth to economic growth is established. Economic growth, energy consumption, and trade openness also each have bidirectional causal effect on financial development. According to statistical data, along with significant projected economic development in CPEC countries, policymakers and regulators are urged to strengthen environmental protection laws in China and Pakistan.
Keywords: 330; Green financial development; Energy Financing; Energy Efficiency; Economic growth; Covid-19 crises; Capital formation